Nilai-Nilai Islam dalam Ruang Lingkup Adat Istiadat Betawi - Al Fahmi, Faiz Fikri; Aisah, Siti; Maysaroh, Siti; Edilah, Selvi; Adawiyah, Robiatul (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
The Betawi community, which is an ethnic gather with a wealthy and different culture. Zakat, which comes from a dialect meaning develop and develop, not as it were serves to extend the compensate for those who carry it out, but too to freed oneself of sin. Within the setting of sharia, zakat plays an critical part in making a difference individuals in require and making social welfare. This ponder employments a subjective expressive strategy to ponder Islamic values in Betawi instruction, as well as how social differences can make questions between devout communities. The Betawi community, as a result of the societies of different tribes, appears that conventional relational unions have a central part in building concordant social relations. Marriage is considered a blessing from God that ties men and ladies to live together in joy and success. In this setting, this article moreover highlights the significance of resilience and concern in a assorted society, in agreement with Islamic lessons that emphasize that contrasts are sunnatullah that must be acknowledged and regarded. Through an in-depth literature review, the creator looks for to extend his understanding of this point, within the trust of contributing to advance investigate on social interaction and devout values in Indonesian society. This inquire about is anticipated to be a reference for future considers related to devout information and the part of zakat in a different society.